2016
DOI: 10.13111/2066-8201.2016.8.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Safety Culture in Modern Aviation Systems – Civil and Military

Abstract: Understanding important aspects of the safety culture should be the main objective for identifying hazards, mitigate and manage risk and find solutions to problems before accidents and incidents occur. The two defining elements of aeronautical decision-making are hazard and risk; risk management is an important component of decisional process and by understanding some issues regarding risk and safety, we will be able to realize the feasible solutions that we may have to apply in flight or ground operations. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Moreover, we indicated that each method can be adapted (the mentioned drawbacks will be addressed). According to the peer reviewed studies [39,69,[111][112][113], the main advantages and drawbacks of the three investigated accidents models are shown in Table 1.…”
Section: Advantages and Drawbacks Of Systemic Methodsmentioning
confidence: 99%
“…Moreover, we indicated that each method can be adapted (the mentioned drawbacks will be addressed). According to the peer reviewed studies [39,69,[111][112][113], the main advantages and drawbacks of the three investigated accidents models are shown in Table 1.…”
Section: Advantages and Drawbacks Of Systemic Methodsmentioning
confidence: 99%